Voltammetric determination of total iron in fuel ethanol using a 1,10 fenantroline/nafion carbon paste-modified electrode - Mattos, Cleiton dos Santos [UNESP]; do Carmo, Devaney Ribeiro [UNESP]; de Oliveira, Marcelo Firmino; Stradiotto, Nelson Ramos [UNESP] (My University, 2008)
This work presents a methodology for iron determination in fuel ethanol using a modified carbon paste electrode with 1.10 fenantroline/nafion. The electrochemical parameters were optimized for the proposed system and the voltammetric technique of square wave was employed for iron determination. An accumulation time of 5 minutes, such as a 100 mV of pulse magnitude (Esw) and frequency (f) of 25 Hz were used as optimized experimental conditions. The modified carbon paste electrode presented linear dependence of amperometric signal with iron concentration in a work range from 6.0x10-6 until 2.0x10-5 mol L-1 of iron, exhibiting a linear correlation coefficient of 0.9884, a detection limit of 2.4 x10-6 mol L-1 (n =3) and amperometric sensibility of 4.5x105 μA/mol L-1. Analytical curve method was used for iron determination at a commercial fuel sample. Flame atomic absorption spectroscopy was employed as comparative technique. © 2008 by ESG.
Keywords: 1,10 fenantroline; Carbon paste electrode; Fuel ethanol; Iron; Square wave voltammetry